Post-anthesis dry matter production and leaf nitrogen distribution are associated with root-derived cytokinins gradient in rice - Kuanyu Zhu; Yuemei Xu; Zhiwei Sun; Yajun Zhang; Weiyang Zhang; Yunji Xu; Junfei Gu; Hao Zhang; Zhiqin Wang; Lijun Liu; Jianhua Zhang; Jianchang Yang (Journal of Integrative Agriculture, 2025)
Aligning leaf nitrogen (N) distribution to match the light gradient is crucial for maximizing canopy dry matter production (DMP) and improving N utilization efficiency. However, the relationship between the gradient of root-derived cytokinins and N distribution in rice leaves and its impact on DMP and the underlying mechanisms remains poorly understood. A two-year field experiment was conducted using two japonica N-efficient varieties (NEVs) and two japonica N-inefficient varieties (NIVs) under four different N rates (0, 90, 180, and 360 kg N ha−1). These selected varieties exhibited similar values in the coefficient of light extinction (KL). Results showed that at lower N rates (0–180 kg N ha−1), the NEVs exhibited greater dry matter weight at maturity, higher grain yield, and improved internal N use efficiency (IEN) compared to the NIVs, despite possessing comparable total N uptake. Compared with the NIVs, the NEVs exhibited a more pronounced nitrogen distribution gradient in leaves, as indicated by the coefficient of nitrogen extinction (KN) values during the middle and early grain-filling stages. This enhanced gradient led to improved coordination between light and nitrogen, resulting in greater photosynthetic production, particularly at lower N rates. Furthermore, the NEVs demonstrated a larger gradient of zeatin (Z)+zeatin riboside (ZR) in leaves (i.e., higher ratios of Z+ZR levels between upper and lower leaves), enhanced expression levels of genes related to N export in lower leaves and Z+ZR loading in the root, respectively, elevated enzymes activities related to N assimilation in upper leaves, in relative to the NIVs. Correlation and random forest analyses demonstrated a strong positive correlation between the Z+ZR gradient, KN, and DMP, and the gradient facilitated the export of N from lower leaves and its assimilation in upper leaves, contributing significantly to both KN and DMP. This process was closely linked to root activity, including root oxidation activity, root Z+ZR content, and Z+ZR loading capacity, as confirmed by applying an inhibitor or a promoter of cytokinins biosynthesis to roots. Interestingly, at the N rate of 360 kg N ha−1, both NEVs and NIVs showed indistinguishable plant traits, achieving a super high-yielding level (over 10.5 t ha−1) but with remarkably low IEN. The results suggest that increasing the Z+ZR gradient can improve KN and DMP, where it needs to maintain higher root activity, thus leading to high yield and high IEN. Further research is needed to explore and develop cultivation practices with reduced N to unlock the super-high-yielding potential of the NEVs.